Development of SpO2 Monitoring System for Early Stroke Detection - Brama Sakti Handoko; Arief Marwanto; Suryani Alifah (Journal of Telematics and Informatics, 2022)
Within this paper, we will discuss about a development process of SpO2 monitoring system that will be used for detecting a patient in the early stage of stroke. This system will measure and compare the SpO2 from both right and left arm at the same time. Stroke patients who experience weakness in the muscles of the one hand can experience different values with hands that do not experience muscle weakness. Stroke patients who are hospitalized with an intravenous infusion in one arm can cause differences in SpO2 values between the right and left fingers. Therefore this measurement method held from that phenomenon. From the monitoring system design, the system should have two sensors to measure the blood saturation, a microcontroller to process the data, and a monitor, buzzer, and micro sd card module to store and display the data. The research shows that the system has been developed and can be used to measure patient’s SpO2 from both hands at the same time, an indicator that will rings when there is an error in the measurement, and a lcd display to show the measurement data. This system also has a microSD card writer to store the measurement data from time to time.